2005
DOI: 10.1038/sj.bjc.6602555
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomised trial to study the role of levamisole and interferon alfa in an adjuvant therapy with 5-FU for stage III colon cancer

Abstract: The purpose of this trial was to examine the efficacy of the addition of levamisole (LEV) or interferon alfa (IFN) to an adjuvant chemotherapy with 5-fluorouracil (5-FU) in patients with stage III colon cancer. According to a 2 Â 2 factorial study design, 598 patients were randomly assigned to one of four adjuvant treatment arms. Patients in arm one received 5-FU weekly for 1 year, patients in arm two 5-FU plus LEV, in arm three 5-FU plus IFN and patients in arm four 5-FU, LEV and IFN. The relative risk of rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Although the detailed mechanism for oxaliplatin-induced TS gene downregulation needs to be further elucidated, our result is concordant with two previous reports (Raymond et al, 2002;Yeh et al, 2004), which indicated that oxaliplatin could downregulate TS in cancer cells and thus potentiate the efficacy of 5-FU. As oxaliplatin and 5-FU have been shown to be highly synergistic not only in preclinical models (Raymond et al, 1997) but also in subsequent clinical trials (Rothenberg et al, 2003;Chao et al, 2004;Lordick et al, 2005;Schippinger et al, 2005;Cavanna et al, 2006), our data provide important information regarding why the combination of oxaliplatin and 5-FU results in better objective response than single use alone.…”
Section: Discussionmentioning
confidence: 74%
“…Although the detailed mechanism for oxaliplatin-induced TS gene downregulation needs to be further elucidated, our result is concordant with two previous reports (Raymond et al, 2002;Yeh et al, 2004), which indicated that oxaliplatin could downregulate TS in cancer cells and thus potentiate the efficacy of 5-FU. As oxaliplatin and 5-FU have been shown to be highly synergistic not only in preclinical models (Raymond et al, 1997) but also in subsequent clinical trials (Rothenberg et al, 2003;Chao et al, 2004;Lordick et al, 2005;Schippinger et al, 2005;Cavanna et al, 2006), our data provide important information regarding why the combination of oxaliplatin and 5-FU results in better objective response than single use alone.…”
Section: Discussionmentioning
confidence: 74%
“…For this purpose, we performed a retrospective biomarker analysis in a prospective randomized cohort of stage III colon cancer patients treated with adjuvant 5FU. The prospective randomized trial (ABCSG-90) was initially reported by the Austrian Breast and Colorectal Cancer Study Group (ABCSG) in 2005 ( Schippinger et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…The utility of interferons has been also demonstrated for the treatment of colon carcinoma in a number of studies, as agents that can be administered alone or in combination with chemotherapeutics [9,28,29]. Dexamethasone was incorporated in our study protocol because steroids are commonly used in the post-operative management of patients undergoing bowel resection due to inflammatory bowel diseases [2,3].…”
Section: Discussionmentioning
confidence: 99%